The Power of Perioperative Online Classrooms - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2019)
Distance (or online) learning and becoming accustomed to new technologies are two challenges educators and educational facilities are facing especially with the plentiful development of web-based technology. Technologically advanced nursing documentation encompasses electronic formats1 and we must keep pace with our educational offerings for today’s nurses. The internet has allowed for many opportunities in education without being physically present in a classroom.2 Perioperative practice environments continue to involve increasing complexity and patient acuity with evidence suggesting higher levels of nursing education have positive effects on nurses, patient care and mortality rate.1 This article presents a background of online perioperative education, an overview of online learning, and its advantages and disadvantages to nurse learners, and outlines significant program elements that should be included in perioperative training.